HEARTSMAP-U: Adapting a Psychosocial Self-Screening and Resource Navigation Support Tool for Use by Post-secondary Students - Virk, Punit; Arora, Ravia; Burt, Heather; Gadermann, Anne; Barbic, Skye; Nelson, Marna; Davidson, Jana; Cornish, Peter; Doan, Quynh (Frontiers in Psychiatry, 2022)
Background: Mental health challenges are highly prevalent in the post-secondary educational setting. Screening instruments have been shown to improve early detection and intervention. However, these tools often focus on specific diagnosable conditions, are not always designed with students in mind, and lack resource navigational support. Objective: The aim of this study was to describe the adaptation of existing psychosocial assessment (HEARTSMAP) tools into a version that is fit-for-purpose for post-secondary students, called HEARTSMAP-U. Methods: We underwent a three-phase, multi-method tool adaptation process. First, a diverse study team proposed a preliminary version of HEARTSMAP-U and its conceptual framework. Second, we conducted a cross-sectional expert review study with Canadian mental health professionals (N=28), to evaluate the clinical validity of tool content. Third, we conducted an iterative series of six focus groups with diverse post-secondary students (N=54), to refine tool content and language, and ensure comprehensibility and relevance to end-users. Results: The adaptation process resulted in the HEARTSMAP-U self-assessment and resource navigational support tool, which evaluates psychosocial challenges across ten sections. In Phase two, clinician experts expressed that HEARTSMAP-U’s content aligned with their own professional experiences working with students. In Phase three, students identified multiple opportunities to improve the tool’s end-user relevance by calling for more “common language,” such as including examples, definitions, and avoiding technical jargon. Conclusions: The HEARTSMAP-U tool is well-positioned for further studies of its quantitative psychometric properties and clinical utility in the post-secondary educational setting.